Pertumbuhan Kambing Kacang Jantan di Desa Kualin Kecamatan Kualin Kabupaten Timor Tengah Selatan - Erwin K. Tasoin (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
TThis research intent to know male bean goat growth that maintained traditional ala by cattleman farmer at Silvan kualin kualin's district Timor's Regency Intermediates south. This research utilize survey method. Started by survey advancing to know breeding ownership state and so long continent. Breed that becomes research object be 41 male bean goats belong to people cattleman with aged different one namely 1 1,5 and 2 years. Variable that is measured in this research covers, wight increase warms up daily, chest circular, long high warm up shoulder. menunjukan's observational result that wight increase warms up male bean goat daily aged 1 1,5 and 2 ala year in a row are 0,087 kg, 0,056 kg. Meanwhile chest circular, long warms up, shoulder high each is 0,078 cm, 0,056 cm, 0,074 cm 0,072 cm, 0,074 cm and 0,057 cm. Conclude this research is aged male bean goat 1 1,5 maintained year on dry season with pemeliharaaan gemabala's system increase fast wight warms up daily, chest circular, long high warm up increase runaway speed shoulder its better of breeding aged male bean goat 2 maintained year on dry season by use of penned system.